(Technical Design and Testing of Chitosan Extractor from Shirmps Shells) - Rizal Alamsyah; Enny Hawani Lubis; Endah Djubaedah (Warta Industri Hasil Pertanian, 2002)
The study was aimed at designing and testing of chitosan (polymer) extractor by demineralization, deproteinization, and deacetylation from shrimps shells. the equipment was generated with induction motor of 0.5hp (horse power) and equipped with liquid heater and thermostat in order to maintain temperature level of the process .the blade or propeller agitator was mounted off center.the demineralization process were conducted at 70-75 0C with choloric acid of 1.25 N and 1.5 hours and 2 hours period of process treatment .meanwhile deproteinization were employed at 80-85 0C using sodium hidroxide 3% w/v in the same hours treatment as the demineralization process. sodium hidroxide of 50% (w/v)was employed in the same hours treatment as the demineralization process .which operated at 100-110 0C in the same hours variation of treatment the result showed that thwe best quality chitosan was obtained with demineralization , and deacetylation process which were conducted for 2 hours and 2 run of each process. these were indicated by viscosity resulted e.g 18000 cps (centipoises